'The party's over': critical junctures, crises and the politics of housing policy. Issue 1 (2nd January 2017) - Jacobs, Keith; Manzi, Tony
Abstract: The key argument set out in this article is that historical and comparative forms of investigation are necessary if we are to better understand the ambitions and scope of contemporary housing interventions. To demonstrate the veracity of our claim, we have set out an analysis of the UK housing polices enacted in the mid-1970s as a basis for comparison with those pursued 40 years later. The article begins with a critical summary of some of the methodological approaches adopted by researchers used to interpret housing policy. In the main section, we present our critical analysis of housing policy reforms (implemented by the Labour government between 1974 and 1979) noting both their achievements and limitations. In the concluding section, we use our interpretation of this period as a basis to judge contemporary housing policy and reflect on the methodological issues that arise from our analysis.